Processamento mínimo de mamão e abacaxi: respostas fisiológicas, bioquímicas e microbiológicas. - Xavier, Viviane Lucas Silva Mansur (2007)
The minimum processing is a way of making to offer the production of a fresh and immediate comsuption product. This way, studies involving physiological, biochemical and microbiological answers of papaya and pineapple minimally processed were realized, in order to keep the product quality and increase the shelf-life. Four experiments were conducted. The papaya and pineapple physical and chemical qualities, submitted to different types of agents sanitizantes, were analyzed: the control, with Ca(OCl)2, radiated with ultraviolet light and with NaOCl. At the end, they were conditioned in packings of PP (52µm) stored in BOD greenhouse. Each two days, the following analyses were accomplished for the experiments: the soluble solids content (SSC), titratable acidity (TA), SSC/TA ratio, pH, loss of fresh matter (PMF), microbiological analyses, vitamin C and activity of the pectinmethylesterase (PME). In the last day, for an experiment with papaya, the preference test. The minimally processed papaya, in general, retained physical and chemical ideal characteristics for consumption, the sanitation agents were efficient for microbiological control and the treatment with Ca(OCl)2 delayed the fruit aging. In the minimum processing of pineapple ‘Pérola ' the treatment with ultraviolet radiation was not recommended, modifying abruptly the metabolism of the fruits. All of the sanitation agents were recommended for microbiological control for 6 days, independent of the temperature and maturation stadium worked the fruits didn't present activity of the pectinametilesterase. The analyzed fruits did not presented pectinmethylesterase activity.